2020
DOI: 10.1016/j.jenvman.2020.110492
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and spectroscopic quality assessment of compost from date palm (Phoenix dactylifera L.) waste valorization

Abstract: In order to increase organic matter availability, date palm waste was co-composted with goat manure according to an industrial ecological approach for a sustainable development. During the composting process, the organic matter biodegradation and compost quality were controlled using physico-chemical and biological parameters associated to spectroscopic techniques. To promote the composting process, date palm waste was previously water soaked in basin for 5 days and the resulted wastewater was used to humidify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…To characterize the DOM, the quality indices, namely speci c absorbance at 254 nm (SUVA 254 ), and absorbance ratios between 250 nm and 365 nm (E 2 /E 3 ), were calculated. The detailed calculation methods are reported elsewhere (Abid et al, 2020;Chen et al, 2017;Guo et al, 2018).…”
Section: Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the DOM, the quality indices, namely speci c absorbance at 254 nm (SUVA 254 ), and absorbance ratios between 250 nm and 365 nm (E 2 /E 3 ), were calculated. The detailed calculation methods are reported elsewhere (Abid et al, 2020;Chen et al, 2017;Guo et al, 2018).…”
Section: Spectral Analysismentioning
confidence: 99%
“…Composting is an environmentally friendly treatment technology for organic wastes from livestock manure, agricultural residues, and municipal solid wastes (Abid et al, 2020;Chen et al, 2017;Huang et al, 2021;Liu et al, 2021). Compost products can be utilized as organic fertilizer for soil, which could be bene cial for the improvement of soil quality and recycling of resources (Fang et al, 2016;Liu et al, 2021;Monda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They were then put to germinate in Petri dishes lined with filter paper moistened with distilled water for the fresh water control Td 10 mL, with saline water for the salty water control Ts, a third case was studied to experiment with the compost effect on salinity, compost extracts were added at different concentrations (10%, 25%, 50% and 75%) for both distilled and salty water. The compost extracts were prepared according to standards (10 g of compost in 100 mL of distilled water) [17].…”
Section: Seed Germinationmentioning
confidence: 99%
“…Toledo et al (2019) reported that co-composting of eggplant waste and sewage sludge had an important impact on odor concentration reduction. Palm waste can be managed by co-composting with sewage and agrifood sludge, but the use of date palm waste may increase the salt contents in the final composts (Vico et al, 2018;Doctor et al, 2020 (Wang and Nie, 2001).…”
Section: Urban Food Waste Compostingmentioning
confidence: 99%